Pengaruh Motivasi dan Disiplin terhadap Kinerja Karyawan PT. Cibaliung Sumberdaya di Kabupaten Padeglang - Risna Dewi; Arif Fadila (Universitas Batanghari, 2022)
PT Cibaliung Sumberdaya as a subsidiary of PT Antam Tbk had reached peak production in 2012 with a total production of 2 tons of dore bullion of gold. However, gold production in the couple years later going the downward trend and rarely reached the target. In this research, the researcher uses three variables: X1 is motivation, X2 is discipline, and Y is performance. The research method used is analysis of descriptive and verification according to the data that taken through questionnaires which have been distributed to employees randomly considering a minimum number of respondents based on the Slovin formula (Sevilla et al., 1960). Based on the research data processing, it is known that the factual conditions of motivation, discipline and employee performance at PT Cibaliung Sumberdaya show poor results. Work motivation and work discipline have a correlation of 65.1% which means there is a strong relationship between that two variables. Work motivation and discipline partially contribute respectively 31.6% and 24.5% to employee performance. Work motivation and work discipline have a simultaneous effect on employee performance by 56.1%, while the remaining 43.9% is the contribution of other variables (ε) that are not considering in the study.